Effect of High Fat Diet on Histopathological Appearance of Pregnant Wistar Rat’s Liver - Desmawati Desmawati; Ruhilmi Nisa; Nita Afriani (Majalah Kedokteran Bandung, 2022)
Indonesia is facing increased consumption of calorie-dense foods, such as fast food, among its society. Changes in diet and physical activities towards unhealthy ones can result in an imbalanced lifestyle, leading to various consequences, including hyperlipidemia. Pregnant women experience significant increases in plasma concentrations of lipids, lipoproteins, and apolipoproteins. Excessive cholesterol levels in pregnant women will result in the formation of fat in the liver. The purpose of this study was to determine the effect of a high-fat diet to pregnant Wistar rats (Rattus norvegicus) on the histopathological features of the liver. A true experimental with post test only control group design was applied in this study, which was conducted from August 2020 to November 2021. Fourteen (14) pregnant female rats were divided into two groups. The first group of rats was fed with a high-fat diet, while the second group, which was the control group, was given a standard diet. The high-fat diet used was 3 mL/rat/day beef brain. After the rats delivered their litters, the rats’ livers were retrieved, then examined histopathologically under a microscope. This research was conducted from No fatty liver was identified in the control group or the treatment group. Hence, a high-fat diet does not affect the liver histopathological features in pregnant Wistar rats.